2005
DOI: 10.1124/jpet.105.091736
|View full text |Cite
|
Sign up to set email alerts
|

Functional Domains of the Mouse β3-Adrenoceptor Associated with Differential G Protein Coupling

Abstract: Alternative splicing of mouse ␤ 3 -adrenoceptor transcripts produces an additional receptor isoform (␤ 3b -adrenoceptor) with a C terminus comprising 17 amino acids distinct from the 13 in the known receptor (␤ 3a -adrenoceptor). We have shown that the ␤ 3b -adrenoceptor couples to both G s and G i , whereas the ␤ 3a -adrenoceptor couples only to G s . To define the regions involved in this differential G protein coupling, we have compared wild-type, truncated, and mutant ␤ 3 -adrenoceptors. In Chinese hamster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 33 publications
4
30
1
Order By: Relevance
“…Expression of the Mouse ␤ 3a -and ␤ 3b -AR and Receptor Mutants in CHO-K1 Cells-Plasmids (pcDNA3.1ϩ) carrying the coding region for each of the ␤ 3a -and ␤ 3b -AR, a truncated ␤ 3 -AR, and the mutant Y392A were as described previously (21,22). Five additional mutants were created to examine the potential importance of residues in the C terminus for G protein coupling.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of the Mouse ␤ 3a -and ␤ 3b -AR and Receptor Mutants in CHO-K1 Cells-Plasmids (pcDNA3.1ϩ) carrying the coding region for each of the ␤ 3a -and ␤ 3b -AR, a truncated ␤ 3 -AR, and the mutant Y392A were as described previously (21,22). Five additional mutants were created to examine the potential importance of residues in the C terminus for G protein coupling.…”
Section: Methodsmentioning
confidence: 99%
“…The ␤ 3a -and ␤ 3b -AR isoforms differ only in their distal C-terminal tail, yet cAMP accumulation mediated by the ␤ 3b -AR is increased following pretreatment of cells with pertussis toxin (PTX), whereas the ␤ 3a -AR response is PTX-insensitive. Use of cellpermeable peptides corresponding to the unique ␤ 3a -and ␤ 3b -AR C termini demonstrated that the ␤ 3a -AR C-terminal tail interacts with a distinct protein or signaling complex (22).…”
mentioning
confidence: 99%
“…Mutation of Ser 755 partially changed the signaling profile of RXFP1, perhaps suggesting that it forms part of a binding motif involving Arg 752 . To examine RXFP1-G␣ i3 signaling further, we disrupted membrane rafts using filipin III (Sato et al, 2007) and showed that RXFP1 coupling to G␣ i3 was dependent upon their presence, whereas RXFP2 signaling was insensitive to membrane raft disruption. Indeed, RXFP2-10ct1 coupling to the G␣ i3 pathway was also prevented by membrane raft disruption, whereas deletion of the final 10 amino acids of the RXFP1 C terminus or substitution of Arg 752 for Ala removed the sensitivity of RXFP1 to membrane raft disruption.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that ␤ 3 -adrenoceptor signaling is influenced by the localization of the receptor within caveolae (Sato et al, 2007). Thus, we tested the effect of membrane raft disruption upon RXFP1 signaling using filipin III (Fig.…”
Section: Rxfp1-g␣ I3 Coupling Depends Upon Arg 752 and Lipid Raftsmentioning
confidence: 99%
“…Likewise, ␤ 3 -AR-mediated Erk1/2 phosphorylation is independent of G i , because the response is insensitive to pertussis toxin, and ␤ 3a -AR do not couple to G i (Hutchinson et al, 2002;Sato et al, 2005).…”
Section: Signaling Pathways Of the Mouse ␤ 3 -Ar 1365mentioning
confidence: 99%